Exploiting Market-Based Mechanisms to Meet Utilities' Energy Efficiency Obligations - Sinton, Jonathan; de Wit, Joeri (World Bank, Washington, DC, 2014)
Electric utilities are key actors in the quest to induce large-scale energy savings among end users. But often it is not enough simply to mandate utilities to achieve a specific target. Three new market-based mechanisms are available for utilities to use in promoting energy efficiency. Historically, mechanisms of demand-side management may be classified as regulatory, policy-based, market-based, and load-targeting. This knowledge note is important, because electric utilities are well-positioned to help raise energy efficiency. The three new market-based mechanisms to help achieve this goal include Establish a white certificates scheme establishing a white certificates scheme, establishing energy efficiency auctions, and establishing energy efficiency feed-in tariffs. These new market-based models are available for utilities to use in promoting energy efficiency, in concert with other means of procurement. Whatever the design, program effectiveness will depend on technically competent and trusted verification of energy savings and their costs, long-term commitment to maintaining the efficiency program, and flexibility in adjusting it over time to ensure that programs keep performing.